Identification of rare-earth minerals associated to K-feldspar: Capacsaya project in Peru - Ochoa, J. (2021)
A recently discovered the rare-earth-rich site in Capacsaya, located at 123 km northwest of Cusco, at the south of Peru, contains significant quantities of light and heavy rare-earth elements such as neodymium, lanthanum, cerium, europium, and yttrium. This work reports the identification of rare-earth elements and their associated minerals using scanning electron microscopy, energy-dispersive X-ray spectroscopy and X-ray diffraction analyses. Five (5) samples extracted from different locations at the Capacsaya site were characterized and identified K-feldspar as the mineral associated with the rare-earth elements in a representative sample with a high concentration of lanthanum and cerium. The results showed rare-earth elements contained within the mineral phase monazite, being cerium the dominant element in the phase (La, Ce, Nd)PO4. Finally, through the electrostatic separation process we demonstrate that it was possible to achieve an efficient separation of the K-feldspar phase in the particle size range 75–150 μ m.